Toughness, Tenacity and Maximum Initial Strength of Rubber Modified Asphalt Binders - Jadidi, K.; Khalili, M.; Karakouzian, M.; Amirkhanian, S. (Engineering, Technology & Applied Science Research, 2019)
The toughness and tenacity test method, which was developed in the 1980s, is popular for evaluating a polymer-modified binder. Several states like Nevada require performing this test to evaluate non-modified binder samples, as well as other types of modified binders. In this regard, a toughness and tenacity test was performed on rubber-modified samples produced from virgin binder PG58-28, PG64-16 and AC-20. In order to take the rubber size, type and content into account, two rubber sizes, mesh #20 and #40, two rubber types, ambient and cryogenic, and three rubber contents, 10%, 15%, and 20% were produced and tested. The results then were compared with polymer-modified and terminally blended rubber-modified samples. The results show improvement in the amount of initial maximum strength, and a decline in the magnitude of elongation, toughness and tenacity for the rubber-modified binder, compared to other types of binders.